2016
DOI: 10.1515/helmin-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

Parasites with possible zoonotic potential in the small intestines of red foxes (Vulpes vulpes) from Northwest Bohemia (CzR)

Abstract: SummaryWe determined the prevalence of primarily zoonotic parasites in the small intestines of 40 (20 males and 20 females) red foxes living near human dwellings. The total prevalence of parasite infection was 77.5 % (31/40); the prevalence was 37.5 % (15/40) for Toxocara canis and 35 % (14/40) for Toxascaris leonina. The mean intensity infection was 3 and 11 helminths for T. canis and T. leonina, respectively. The prevalence of other intestinal helminths and mean infection intensity in this study are given: E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…A wide distribution of Mesocestoides spp., mainly in a significant prevalence (27–68%), was confirmed by reports from many other European countries, i.e. Hungary [ 32 ], the Czech Republic [ 8 ], Denmark [ 5 , 6 ], Slovenia [ 33 ] and eastern Germany [ 7 , 34 ]. An absence or low prevalence of Mesocestoides spp.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A wide distribution of Mesocestoides spp., mainly in a significant prevalence (27–68%), was confirmed by reports from many other European countries, i.e. Hungary [ 32 ], the Czech Republic [ 8 ], Denmark [ 5 , 6 ], Slovenia [ 33 ] and eastern Germany [ 7 , 34 ]. An absence or low prevalence of Mesocestoides spp.…”
Section: Discussionmentioning
confidence: 53%
“…Research in other European countries showed a moderately high or low prevalence of A. alata (5.5–31.4%) [ 3 , 6 , 7 , 37 , 38 , 40 , 41 ]. In some studies conducted in Europe, these trematodes were not found at all [ 8 , 9 , 35 , 36 , 39 ]. Our data showed that in regions with a high prevalence, the intensity of the infection was higher than that in regions with a low prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, similar levels of occurrence of nematodes were observed between males and females. Similarly, previous studies have also failed to note any difference in occurrence based on sex (2,30,52). High prevalence of nematode has been observed in foxes inhabiting the region of north-west Poland.…”
Section: Discussionmentioning
confidence: 77%
“…A number of studies suggest that the occurrence of geohelminths is associated with climate conditions (temperature, air and soil humidity, mean annual rainfall) that extend the lifespan of their free-living developmental stages (1,2,53,54,55). The region of north-west Poland is situated close to the sea, has substantial forest cover and a temperate climate, as well as a total annual rainfall of 500-800 mm and a mean annual temperature of 7-9 °C, as well as significant air humidity, indicating that this area supports the development of parasites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation